Analyzing power and cross section distributions of the 12C (p,pα)8Be cluster knockout reaction at an incident energy of 100 MeV - Mabiala, Justin (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Physics))--University of Stellenbosch, 2010.